Stres dan Kesejahteraan Psikologis pada Ibu Bekerja: Peran Moderasi Mindful Parenting - Rinaldi, Martaria Rizky; Hardika, Jelang (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2025)
Employment provides economic and psychological benefits for mothers but also presents significant challenges that can impact psychological well-being. This study aims to explore the effects of mindful parenting and stress on the psychological well-being of working mothers. This research tests the hypothesis that mindful parenting can improve psychological well-being and that stress can decrease it, with mindful parenting serving as a moderator in this relationship. Using a cross-sectional design, data were collected from 87 working mothers via an online questionnaire. Analysis results show that mindful parenting has a significant positive effect on psychological well-being (p 0.001), while stress has a significant negative effect (p = 0.047). However, the interaction between stress and mindful parenting was not significant (p = 0.995). These findings suggest that mindful parenting plays an important role in enhancing psychological well-being, although it may not moderate the impact of stress. The study contributes to the literature by highlighting the role of parenting mindfulness as a positive factor in working mothers’ mental health. Future research using longitudinal or experimental designs is recommended to assess causal relationships and to explore other protective factors such as resilience and social support that may interact with stress and parenting.